Strong Provincial Leadership: Concept and Typology in Buenos Aires Peronism (1983-2015) (Colección, 2018)
This article explores different styles of Peronist leadership in Buenos Aires, their impact on provincial partisan behavior, and the necessary conditions for the emergence of strong leadership. At the same time, it throws light on two reasons, which justify this case study. Firstly, it underlines Buenos Aires´s unquestioned relevance in Argentinean politics, its particular overlapping at national level, and its lack of autonomy in relation to federal power (Ollier: 2010). These features make this province determining when it comes to understanding the country´s governability. Secondly, it is based on three statements: Buenos Aires Peronism is the only party which governed uninterruptedly for twenty-eight years; its electoral national stronghold is located in greater Buenos Aires; and the political struggle for the party´s national leadership takes place mainly in Buenos Aires.The hypothesis suggests that Strong Provincial Leadership (SPL) keeps Buenos Aires Peronist party united, beyond the Peronist president’s strength. On the contrary, weak provincial leadership gives way to the emergence of splinter factions, leading to far reaching consequences nationwide. In an attempt to test this hypothesis, we define SPL, point out its attributes and operationalize them in the presence and absence of SPL, so as to build a typology that compares styles of leadership, i.e. this is a conceptual article with an empirical illustration.
Keywords: Strong Provincial Leadership; Typology of Provincial Leadership; Buenos Aires Peronist Party; Partisan Fragmentation; Party Unity